Comparação do perfil das retratações na área de engenharia com as demais áreas do conhecimento: um estudo em artigos retratados na base de dados Web of Science no ano de 2020 - Sierdovski, Marcia (2024)
The objective of the study is to compare the profile of retractions of scientific articles in the area of Engineering (technology) with other areas of knowledge, through publications indexed in the Web of Science database, in the year 2020. The search was carried out for documents that contained in the titles the keywords “retraction” OR “retracted” OR “redress” OR “withdrawal” to map the retracted publications in the areas of knowledge of engineering, life sciences and biomedicine, physical sciences, social sciences and arts and humanities. In the first stage, the articles were downloaded and exported to an Excel spreadsheet, totaling 1977 records. In the next stage, articles that did not have their registration in the Retraction Database were excluded, leaving 1531 articles for analysis. The research is classified as quantitative and descriptive with the application of statistical tests and data mining to identify the reasons why the articles are retracted, time of retraction, impact factor, affiliation, COPE, continent and countries of publications, number of authors, language and citations. The study is justified by the relevance of the theme, which addresses a current and critical problem that affects both the engineering field and others. Unethical practices and misconduct have repercussions on segments of society, affecting the whole, where scientific studies are essential for the development, growth and evolution of the world. The results indicate that the engineering field has a considerable number of retractions, and belonging to COPE is a predominant characteristic in the areas in which the journals have a JCR considered high. The most common reasons for retraction were problems with the data and/or results, with a significant average, and the publication occurred in English, on the European continent, frequently in countries such as the USA and England. The profile of retractions highlights influential variables such as the number of authors, history of previous retractions, reasons, JCR and affiliation with COPE to reduce retractions. It is concluded that retractions have a tendency to increase, but the implications of the study findings have positive aspects in practical application when following the instructions already established by COPE, which are considered standard in publication ethics. And COPE, as the central body, should create strategies to minimize new retractions, through standardization of guidance for retraction in editorial policy practices, associated journals, monitoring of the ethical behavior of authors and the obligation of universities to provide training to academics.